Alberta Labour History Institute (ALHI): Workers' History, Workers' Stories (Alberta Labour History Institute (ALHI), 1999)
The Alberta Labour History Institute collects, preserves, and disseminates the stories of Alberta’s working people and their organizations. This website includes full transcripts, podcasts, and profiles of our interviewees. It also includes videos, booklets, themed essays, annual calendars, and a link to a book created by ALHI. –Website description